Hydatidosis in Portugal: a mitochondrial phylogeny approach - Beato, Sílvia (2011)
Hydatidosis is a worldwide zoonosis caused by the larval stage of the tapeworm Echinococcus granulosus. The taxonomy and phylogeny of the genus Echinococcus has been a controversial issue for several years but with the usage of molecular tools to characterize the etiological agents these aspects had been clarified and a new classification has been proposed and is now widely accepted. The aim of this work is to determine the range of genetic variability within and between Portuguese E. granulosus isolates. The Portuguese isolates obtained from sheep and goats were characterized using mitochondrial COI gene sequencing. The sequences were aligned and compared with those present in the GenBank. Preliminary results showed that the Portuguese isolates were E. granulosus sensu stricto (G1-G3 cluster). In addition, phylogenetic analysis of E. granulosus isolates, using the mitochondrial NDI and Cob partial genes, was performed using neighbour-joining (Kimura 2-parameter correction) and Bayesian analyses. The findings showed some degree of variance within single isolates and a significant degree of variance between the cluster G1-G3, where our isolates were, and the other Echinococcus sp.. Despite the variance found among Portuguese isolates, they were all localized within one robust cluster.